Positive electrode active material and application thereof
By using LiVPO4F and carbon materials in the positive electrode active materials of lithium-ion batteries, the fluorine element content and particle size ratio are controlled, and the problem of insufficient discharge performance and cycle stability of lithium-ion batteries under low temperature conditions is solved, and a higher level of Low temperature discharge performance and cycle stability.
Patent Information
- Application Number
- CN202411537828.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
Existing lithium-ion batteries have poor discharge performance and cycle stability under low temperature conditions, especially the electronic conductivity of lithium fluorine vanadium phosphate materials, which affects the low temperature discharge capacity and cycle stability of the battery.
The positive electrode active material including LiVPO4F as the matrix material and carbon material as the cladding layer is used. This material improves the low-temperature discharge performance and cycle stability of the battery by controlling the mass percentage content of fluorine elements and the particle size ratio.
It effectively improves the discharge performance and cycle stability of lithium-ion batteries under low temperature conditions, and improves the energy density and instantaneous high-power discharge capability of low temperatures.
Smart Images

Figure CN119400827A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a positive electrode active material, in particular to a positive electrode active material and an application thereof. Background Art
[0002] At present, phosphate positive electrode materials can be applied to high voltage systems to meet the needs of high energy density, such as LiVOPO4, LiVPO4F, Li2NiPO4F, Li2CoPO4F, etc. However, the LiMnPO4 has the Jahn-Teller effect, which leads to poor structural stability of the material and the actual capacity is far lower than the theoretical value; while the voltage of the Co and Ni phosphate series positive electrode materials is relatively high (about 5V), and there is currently no suitable electrolyte and positive and negative electrode system, so there is no practical application scenario for the time being. The voltage platform of LiVPO4F is higher than that of LiFePO4, the energy density is higher, and the ion conductivity is better than that of conventional iron lithium materials. It has a stable structure and is one of the preferred future lithium-ion battery positive electrode materials. However, lithium vanadium fluorophosphate has poor electronic conductivity, which will affect the discharge capacity and cycle stability of the battery at low temperatures. Summary of the invention
[0003] In view of the above-mentioned defects, the present invention provides a positive electrode active material, which can effectively improve the low-temperature discharge performance and cycle stability of the battery.
[0004] The present invention also provides a positive electrode sheet, comprising the positive electrode active material, so the positive electrode sheet is used in a lithium ion battery to effectively improve the low temperature discharge performance and cycle stability of the battery.
[0005] The present invention provides a lithium ion battery, comprising the positive electrode active material or the positive electrode sheet, so the lithium ion battery has higher low-temperature discharge performance and cycle stability.
[0006] The present invention provides a positive electrode active material, the positive electrode active material comprises primary particles and secondary particles formed by agglomeration of the primary particles; the primary particles comprise a matrix material and a coating layer, the matrix material comprises LiVPO4F, and the coating layer comprises a carbon material;
[0007] The mass percentage of fluorine element in the positive electrode active material is 10wt%-20wt%;
[0008] The ratio of the average particle size of the secondary particles to the average particle size of the primary particles is 15-30.
[0009] Furthermore, the average particle size of the secondary particles is 1 μm-40 μm, and / or the average particle size of the primary particles is 200 nm-500 nm.
[0010] Furthermore, the mass percentage of vanadium in the positive electrode active material is 20wt%-30wt%;
[0011] And / or, the mass percentage of the carbon material in the positive electrode active material is 1wt%-3wt%;
[0012] and / or, the carbon material comprises at least one of soft carbon, graphite, hard carbon, graphene, and carbon nanotubes;
[0013] Preferably, the carbon material comprises soft carbon.
[0014] Furthermore, the positive electrode active material satisfies Formula 1,
[0015] 1≤a / b≤1.2 Formula 1
[0016] In Formula 1, a is the length of the major axis of the secondary particle, in μm; b is the length of the minor axis of the secondary particle, in μm;
[0017] Preferably, the length a of the major axis of the secondary particles is 0.5 μm to 50 μm, and / or the length b of the minor axis of the secondary particles is 0.5 μm to 50 μm.
[0018] Furthermore, the coating layer has a thickness of 1 nm-30 nm.
[0019] Further, the particle size Dv50 of the secondary particles is 5 μm-20 μm, and the particle size Dv90 is 30 μm-40 μm;
[0020] And / or, the specific surface area of the secondary particles is 12m 2 / g-25m 2 / g;
[0021] And / or, the mechanical strength of the secondary particles is 30 MPa-80 MPa.
[0022] The present invention also provides a positive electrode sheet, the positive electrode sheet comprising any one of the positive electrode active materials described above;
[0023] Preferably, the moisture content of the positive electrode sheet is less than 1000 ppm.
[0024] The present invention also provides a lithium-ion battery, which comprises any one of the above-mentioned positive electrode active materials or the above-mentioned positive electrode sheet.
[0025] Furthermore, the lithium-ion battery also includes an electrolyte; the electrolyte includes vinylene carbonate;
[0026] The mass percentage of the vinylene carbonate in the electrolyte is 0.1wt%-10wt%;
[0027] More preferably, the mass percentage of the vinylene carbonate in the electrolyte is 0.1wt%-2wt%.
[0028] Furthermore, the lithium-ion battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector;
[0029] The negative electrode active material in the negative electrode active material layer includes graphite and hard carbon;
[0030] Preferably, the mass ratio of graphite to hard carbon is 2:8-5:5;
[0031] Preferably, the particle size Dv50 of the hard carbon is 3 μm-10 μm, and / or the specific surface area is 5 m 2 / g-10m 2 / g.
[0032] The positive electrode active material of the present invention comprises a matrix material LiVPO4F and a carbon material coated on at least a portion of the surface of the matrix material. By controlling the mass percentage of fluorine element in the matrix material and the ratio of the average particle size of secondary particles to primary particles in the positive electrode active material, the mass content of fluorine element is between 10wt% and 20wt%, and the ratio of the particle size is between 15 and 30, the low-temperature discharge performance and cycle stability of the battery can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the major and minor axes of primary particles in the positive electrode active material of the present invention;
[0034] Figure 2 is a charge and discharge curve diagram of the lithium ion battery in Example 1 of the present invention;
[0035] Figure 3 The cold start terminal voltage bar graph of the lithium ion battery in Example 1 and Comparative Example 1;
[0036] Figure 4 is a SEM image of the positive electrode active material in Example 1 of the present invention at 1.00K;
[0037] Figure 5 This is a SEM image of the positive electrode active material in Example 1 of the present invention at 2.50K;
[0038] Figure 6 This is a SEM image of the positive electrode active material in Example 1 of the present invention at 30.0K;
[0039] Figure 7 This is an EDS image of the V element of the positive electrode active material in Example 1 of the present invention;
[0040] Figure 8 This is an EDS image of the P element of the positive electrode active material in Example 1 of the present invention;
[0041] Fig. 9 This is an EDS image of the O element of the positive electrode active material in Example 1 of the present invention;
[0042] Fig.10 This is an EDS image of the C element of the positive electrode active material in Example 1 of the present invention;
[0043] Fig.11 This is an EDS image of the F element of the positive electrode active material in Example 1 of the present invention;
[0044] Fig.12 This is a TEM image of primary particles in the positive electrode active material in Example 6 of the present invention. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The first aspect of the present invention provides a positive electrode active material, which includes primary particles and secondary particles formed by agglomeration of the primary particles; the primary particles include a matrix material and a coating layer, the matrix material includes LiVPO4F, and the coating layer includes a carbon material;
[0047] The mass percentage of fluorine element in the positive electrode active material is 10wt%-20wt%;
[0048] The ratio of the average particle size of the secondary particles to the average particle size of the primary particles is 15-30.
[0049] Illustratively, the mass percentage of fluorine element in the positive electrode active material is 10 wt %, 12 wt %, 14 wt %, 16 wt %, 18 wt % or 20 wt %.
[0050] Illustratively, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles is 15, 18, 21, 24, 27 or 30.
[0051] It can be understood that the secondary particles in the present invention are formed by agglomeration of primary particles, and the coating layer is disposed on at least a portion of the surface of the base material.
[0052] The mass percentage of fluorine in the positive electrode active material of the present invention can be obtained by ion chromatography, and can be obtained by the following methods:
[0053] The positive electrode active material powder is taken, pickled with hydrochloric acid to remove impurities, filtered to obtain a solid phase, and the solid phase is subjected to IC oxygen bomb combustion treatment. The combustion product is collected for ion chromatography analysis to test the mass percentage of fluorine element in the positive electrode active material.
[0054] The positive electrode active material in the present invention can effectively improve the low-temperature discharge capacity and cycle stability of the battery. The inventor analyzed this phenomenon and believed that the reason may be: a carbon coating layer is set on the surface of the primary particles, which can establish a continuous conductive network in the pole piece, reduce the internal resistance of the material, thereby significantly reducing polarization and effectively improving the low-temperature discharge performance of the battery. Further, the incorporation of fluorine can change the crystal structure of the material. The size and electronegativity of the fluorine element make the crystal lattice spacing of the material appropriate, and its electronegativity changes the distribution and movement of electrons in the material, thereby optimizing the electronic structure of the material and forming a channel in the pole piece that is more conducive to the diffusion of lithium ions. At the same time, the appropriate ratio of the average particle size of the secondary particles to the primary particles allows better contact between the primary particles, forming a more effective lithium ion migration channel, and reducing the contact area between the electrolyte and the positive electrode material, reducing the interface impedance, and combining the increase in the fluorine content. It can form an excellent ion and electron conduction network, realize rapid insertion and removal of lithium ions at low temperatures, effectively improve the ionic conductivity and electronic conductivity of the positive electrode material, and improve the discharge performance and cycle stability of lithium-ion batteries at low temperatures.
[0055] In addition, when the mass percentage of fluorine element in the positive electrode active material is within the aforementioned range, the voltage platform of the battery can be effectively improved, thereby increasing the energy density of the battery.
[0056] In a specific embodiment, the average particle size of the secondary particles is 1 μm-40 μm. Within this range, the positive electrode active material has good processability, and the secondary particles have a relatively large particle size and a small specific surface area, which can ensure the structural stability of the material during the cyclic charge and discharge process.
[0057] Illustratively, the average particle size of the secondary particles is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0058] The "average particle size of the secondary particles" in the present invention is obtained by SEM testing. Specifically, a SEM photograph of the secondary particles is taken at 1000 times magnification, the particle size of the secondary particles in the SEM photograph is tested, and the average value is taken to obtain the average particle size of the secondary particles.
[0059] In a specific embodiment, the average particle size of the primary particles is 200nm-500nm. For example, the particle size of the primary particles is 200nm, 230nm, 260nm, 290nm, 320nm, 350nm, 380nm, 410nm, 440nm, 470nm or 500nm. Within this range, the diffusion path of lithium ions during charging and discharging can be further shortened, and the concentration polarization during low-temperature discharge can be reduced, so that the battery has a higher discharge voltage platform at low temperatures. At the same time, more capacity can be exerted at low temperatures, which is conducive to improving the energy density of the battery.
[0060] The "average particle size of primary particles" in the present invention can be obtained by SEM testing. Specifically, a SEM photograph of the surface of the positive electrode active material particles is taken at 30,000 times, the particle size of the primary particles in the SEM photograph is measured, and the average value is taken to obtain the average particle size.
[0061] In a specific embodiment, the mass percentage of vanadium in the positive electrode active material is 20wt%-30wt%. For example, the mass percentage of vanadium in the positive electrode active material is 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%. Within this range, the charge and discharge platform of the battery at low temperature can be effectively improved, thereby improving the instantaneous high-power discharge capacity at low temperature, which is beneficial to the instantaneous start-up and power performance of the starting battery at low temperature.
[0062] The mass percentage of vanadium element in the positive electrode active material of the present invention can be obtained by ICP testing. The testing method is the same as that described above and will not be described in detail here.
[0063] In a specific embodiment, the mass percentage of the carbon material in the positive electrode active material is 1wt%-3wt%. For example, the mass percentage of the carbon material in the positive electrode active material is 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%. Within this range, the carbon coating on the surface of the positive electrode material is relatively complete and has a low weight ratio, which does not affect the energy density of the battery.
[0064] The mass percentage of the carbon material in the positive electrode active material of the present invention can be obtained by testing with a carbon-sulfur analyzer.
[0065] In a specific embodiment, the carbon material includes at least one of soft carbon, graphite, hard carbon, graphene, and carbon nanotubes;
[0066] Preferably, the carbon material comprises soft carbon.
[0067] When the carbon material includes the aforementioned substances, the electronic conductivity of the positive electrode active material can be further improved, thereby effectively reducing the internal resistance of the material and enabling the battery to have higher low-temperature discharge performance.
[0068] Further preferred is soft carbon, which, compared with other carbon materials, can achieve a higher degree of graphitization at temperatures below 1000°C, achieve a better coating effect, improve the continuity of the coating, and make the positive electrode active material have higher conductivity; at the same time, it can also well adapt to the volume change during the charge and discharge process, which is beneficial to improve the cycle life of the battery.
[0069] When the carbon material is a mixture of the aforementioned multiple substances, the present invention does not specifically limit the ratio between the specific substances.
[0070] In a specific embodiment, the positive electrode active material is a spherical particle, and the positive electrode active material satisfies Formula 1:
[0071] 1≤a / b≤1.2 Formula 1
[0072] In Formula 1, a is the length of the major axis of the secondary particle, in μm; b is the length of the minor axis of the secondary particle, in μm.
[0073] Illustratively, a / b is 1, 1.05, 1.1, 1.15, 1.2.
[0074] The “long axis length” and “short axis length” in the present invention refer to the dimensions obtained based on the scale in the SEM image of the secondary particles.
[0075] like Figure 1 As shown, it is a standard circle, whose major axis length a and minor axis length b are equal, that is, a / b is 1. It is well known in the art that the larger the a / b ratio is, the more it deviates from a circle. The positive electrode active material of the present invention satisfies: 0.8≤a / b≤1.2, which means that the positive electrode active material of the present invention has a spherical or quasi-spherical structure.
[0076] When the positive electrode active material conforms to Formula 1, the positive electrode active material can have a lower initial charge transfer impedance (Rct), which helps to reduce the interface impedance and further improve the low-temperature discharge performance of the battery; at the same time, the contact between the particles is good, further reducing the ohmic internal resistance.
[0077] Preferably, the length a of the major axis of the secondary particles is 0.5 μm to 50 μm, and / or the length b of the minor axis of the secondary particles is 0.5 μm to 50 μm.
[0078] Exemplarily, the major axis length a is 0.5 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm.
[0079] Exemplarily, the minor axis length b is 0.5 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm.
[0080] In a specific embodiment, the coating layer has a thickness of 1 nm to 30 nm. For example, the coating layer has a thickness of 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm or 30 nm. As an inactive substance, a carbon coating layer with too high a content or too thick a coating layer will reduce the content of active substances in the positive electrode material and affect the energy density of the battery. Within this range, not only a high electronic conductivity can be guaranteed, but also the loss of energy density can be reduced, so that the battery has a high cold start performance and a high energy density.
[0081] The thickness of the coating layer in the present invention can be obtained by TEM testing.
[0082] In a specific embodiment, the particle size Dv50 of the secondary particles is 5 μm-20 μm, and the particle size Dv90 is 30 μm-40 μm. Within this range, large particles and small particles are mixed and distributed in the positive electrode active material, which is conducive to mutual filling in the spatial position, improving the compaction density of the pole piece, and thus improving the energy density of the battery.
[0083] Exemplarily, the particle size Dv50 is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.
[0084] Illustratively, the particle size Dv90 is 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm or 40 μm.
[0085] Dv50 in the present invention refers to the particle size corresponding to when the cumulative particle size distribution percentage of the positive electrode active material reaches 50%; Dv90 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the positive electrode active material reaches 90%.
[0086] The Dv50 and Dv90 in the present invention can be obtained by testing with a laser particle size analyzer.
[0087] In one embodiment, the specific surface area of the secondary particles is 12 m 2 / g-25m 2 / g. Within this range, the specific surface area is small, which can further reduce the contact area between the electrolyte and the positive electrode material, reduce the interface impedance, and reduce the occurrence of side reactions between the electrolyte and the positive electrode material, thereby further improving the cold start performance and cycle performance of the battery; at the same time, it can also reduce the water absorption rate of the positive electrode material, improve the gel problem in the preparation process of the positive electrode slurry, and improve the processing performance.
[0088] For example, the specific surface area is 12 m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g or 25m 2 / g.
[0089] The specific surface area in the present invention is obtained by testing with a specific surface area tester.
[0090] In a specific embodiment, the mechanical strength of the secondary particles is 30MPa-80MPa. Specifically, the ratio of the average particle size of the secondary particles to the primary particles, the specific surface area of the secondary particles, the Dv50 and Dv90 of the secondary particles can be controlled by adjusting the slurry particle size Dv50 during the preparation process, the air inlet temperature, the air outlet temperature and the compressed air pressure during the spray drying, and the sintering conditions, so that the mechanical strength of the secondary particles is between 30MPa-80MPa. Within this range, the strength of the positive electrode active material particles is high, which can avoid the material from breaking during rolling or circulation, and further reduce the side reactions between the electrolyte and the active material.
[0091] Illustratively, the mechanical strength of the secondary particles is 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, 75 MPa or 80 MPa.
[0092] The mechanical strength of the present invention can be tested by a micro compression tester.
[0093] In one specific embodiment, the positive electrode active material is prepared by the following method:
[0094] Raw materials including a phosphorus source, a vanadium source, a lithium source, a fluorine source and a carbon source are added to a liquid dispersant and uniformly mixed to obtain a mixed slurry; the mixed slurry is ground to obtain a ground product; the ground product is spray-dried and sintered in sequence to obtain a positive electrode active material.
[0095] Furthermore, by controlling the grinding conditions during the grinding process, for example, the grinding speed and the grinding time, the particle size of the grinding product is further controlled, thereby controlling the average particle size of the primary particles in the positive electrode active material.
[0096] Preferably, the particle size Dv50 of the ground product is 200 nm to 400 nm, which helps to make the average particle size of the primary particles in the positive electrode active material be 200 nm to 500 nm.
[0097] Furthermore, by controlling the conditions during the spray drying process, including controlling the solid content of the ground product between 30% and 40%, the spray drying inlet air temperature at 150°C to 250°C, and the outlet air temperature at 80°C to 250°C, the a / b, particle size distribution, specific surface area and mechanical strength of the positive electrode active material can be further controlled.
[0098] Furthermore, by controlling the amount of fluorine source added to the raw material, the mass percentage of fluorine element in the positive electrode active material is further controlled to be between 10wt% and 20wt%.
[0099] Furthermore, by controlling the added amounts of the vanadium source and the carbon source in the raw material, the mass percentages of the vanadium element and the carbon material in the positive electrode active material can be further controlled.
[0100] Furthermore, by controlling the sintering temperature and sintering time, the crystal structure stability of the positive electrode active material is further improved. Preferably, the product after spray drying is heated to 700°C-850°C at a heating rate of 2°C / min-5°C / min in a nitrogen atmosphere, kept warm for 8h-25h, and then cooled to room temperature at a cooling rate of 2°C / min-5°C / min to obtain the positive electrode active material.
[0101] The phosphorus source in the present invention refers to a raw material that provides the phosphorus element, the vanadium source refers to a raw material that provides the vanadium element, the lithium source and the fluorine source refer to raw materials that provide the fluorine element, and the carbon source refers to a raw material that provides the carbon element. As long as they contain the target elements (P, V, F, C), they are all within the scope of the present invention.
[0102] The present invention does not specifically limit the types of phosphorus source, vanadium source, lithium source, fluorine source and carbon source. For example, the phosphorus source can be selected from at least one of phosphoric acid, lithium phosphate, ammonium dihydrogen phosphate, phosphorus pentoxide, red phosphorus, white phosphorus and sodium phosphate; the vanadium source can be selected from at least one of ammonium metavanadate, vanadium pentoxide and sodium vanadate; the lithium source can be selected from at least one of lithium carbonate, lithium phosphate, lithium fluoride and lithium hydroxide; the fluorine source can be selected from at least one of lithium fluoride, polytetrafluoroethylene, sodium fluoride and hydrofluoric acid; the carbon source can be selected from at least one of glucose, sucrose, PEG, polyethylene glycol, polyvinyl alcohol, PVP, asphalt, phenolic resin and cyclodextrin.
[0103] Among them, the carbon source only needs to be able to decompose at the sintering temperature to ensure the uniformity and integrity of the carbon material coating on the surface of the matrix material LiVPO4F during the high-temperature sintering process.
[0104] When the above five types of compounds are mixtures of multiple specific compounds, the present invention does not impose too many restrictions on the ratios between the specific compounds.
[0105] A second aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising the positive electrode active material of the first aspect;
[0106] Preferably, the moisture content of the positive electrode sheet is less than 1000 ppm.
[0107] Since the positive electrode sheet includes the aforementioned positive electrode active material, the positive electrode sheet is used in a lithium-ion battery to effectively improve the cold start performance and cycle stability of the battery.
[0108] Preferably, the water content of the positive electrode sheet is less than 1000ppm. Specifically, the thickness of the carbon material coating layer in the positive electrode active material can be controlled during the preparation process to further improve the water absorption problem of the material; at the same time, the water content in the positive electrode sheet can be reduced by controlling the storage conditions of the positive electrode active material and the ambient humidity during the slurrying process, thereby making the water content of the positive electrode sheet less than 1000ppm.
[0109] In one embodiment, the surface density of the positive electrode sheet is 6 mg / cm 2 -12mg / cm 2 In this range, the positive electrode active material is in good contact with the positive electrode current collector, and the diffusion path of lithium ions is further shortened, the battery ohmic internal resistance and concentration polarization are reduced, which is conducive to further improving the battery's charge and discharge performance and cycle performance at low temperatures.
[0110] For example, the surface density is 6 mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm2 、11mg / cm 2 or 12 mg / cm 2 .
[0111] The surface density of the positive electrode sheet in the present invention refers to the single-sided coating surface density, and the double-sided coating surface density is 12 mg / cm 2 -24mg / cm 2 .
[0112] In one embodiment, the compaction density of the positive electrode sheet is 1.6 g / cm 3 -2.3g / cm 3 Within this range, not only can the energy density of the battery be guaranteed, but also the contact between the positive electrode active particles can be good, the battery ohmic internal resistance can be reduced, and the polarization at low temperatures can be reduced.
[0113] For example, the compacted density is 1.6 g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 or 2.3g / cm 3 .
[0114] In a specific embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector;
[0115] The positive electrode active material layer includes, by mass percentage, 90wt%-95wt% of positive electrode active material, 2.5wt%-5wt% of conductive agent, 2.5wt%-4wt% of binder, and 0wt%-1wt% of dispersant. Within this range, on the one hand, the positive electrode active particles and the positive electrode active layer and the positive electrode current collector can be well bonded, and can stably adhere to the surface of the current collector; on the other hand, it can ensure that the conductive agent is sufficient, effectively reduce electrochemical polarization, and is conducive to improving the instantaneous discharge capacity at low temperatures; on the other hand, it can avoid the problem of a sharp increase in the viscosity of the positive electrode active layer slurry during the static process.
[0116] Preferably, the thickness of the positive electrode collector in the positive electrode sheet is 8 μm-16 μm, for example, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm.
[0117] The present invention does not specifically limit the types of conductive agent, binder, and dispersant, and conventional selections in the art can be adopted. For example, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, graphene, metal powder, and carbon fiber; the binder includes at least one of polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), and styrene-butadiene rubber (SBR); the dispersant includes at least one of polyethylene glycol (PEG), sodium carboxymethyl cellulose (CMC-Na), and polyvinyl alcohol (PVA).
[0118] A third aspect of the present invention provides a lithium ion battery. Since the lithium ion battery includes the positive electrode active material of the first aspect or the positive electrode sheet of the second aspect, the battery has higher low-temperature discharge performance and cycle performance.
[0119] In a specific embodiment, the lithium ion battery further comprises an electrolyte; the electrolyte comprises vinylene carbonate;
[0120] Preferably, the mass percentage of vinylene carbonate in the electrolyte is 0.1wt%-10wt%;
[0121] More preferably, the mass percentage of vinylene carbonate in the electrolyte is 0.1wt%-2wt%.
[0122] Illustratively, the mass percentage of vinylene carbonate in the electrolyte is 0.1 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%.
[0123] When the electrolyte in the lithium-ion battery includes vinylene carbonate and its mass percentage in the electrolyte is controlled within the aforementioned range, it helps the formation of the positive electrode interface film CEI film, improves the structural stability of the positive electrode active material, and can increase the electronic and ionic conductivity, further improving the low temperature performance and cycle performance of the battery.
[0124] In a specific embodiment, the electrolyte further includes a lithium salt, an organic solvent and an additive;
[0125] Preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bisfluorosulfonyl imide and lithium bistrifluoromethanesulfonyl imide; more preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bisfluorosulfonyl imide and lithium bistrifluoromethanesulfonyl imide;
[0126] More preferably, the mass percentage of lithium salt in the electrolyte is 8wt%-18wt%;
[0127] Preferably, the organic solvent comprises carboxylates and carbonates;
[0128] Preferably, the additive includes fluoroethylene carbonate; more preferably, the mass percentage of fluoroethylene carbonate in the electrolyte is 0.1wt%-10wt%.
[0129] Illustratively, the mass percentage of lithium salt in the electrolyte is 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 16wt%, 17wt% or 18wt%.
[0130] Illustratively, the mass percentage of fluoroethylene carbonate in the electrolyte is 0.1 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%.
[0131] Since the positive electrode active material in the present application has a high voltage platform, the electrolyte is prone to side reactions under high temperature storage conditions, generating gas, causing the battery to swell and cause safety issues. When the electrolyte in the lithium-ion battery further includes the above-mentioned lithium salt, solvent and additive, it can be more compatible with the positive electrode active material, and the fluoroethylene carbonate in the electrolyte can form an interface film on the positive electrode, further improving the structural stability of the positive electrode active material, and can improve the electronic and ionic conductivity, so that the battery has higher low temperature performance and cycle performance.
[0132] In a specific embodiment, the lithium-ion battery further comprises a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector;
[0133] The negative electrode active material in the negative electrode active material layer includes graphite and hard carbon.
[0134] Since the interlayer spacing of hard carbon materials is greater than that of graphite, the use of negative electrode sheets mixed with graphite and hard carbon can effectively increase the rate of lithium ion extraction and deintercalation at the negative electrode, thereby improving the kinetic properties of lithium-ion batteries. In particular, at low temperatures, the rate of lithium ion migration decreases significantly. When the above-mentioned negative electrode sheet is combined with the positive electrode active material in the present invention, the high-rate discharge characteristics of lithium-ion batteries at low temperatures can be significantly improved.
[0135] Preferably, the mass ratio of hard carbon to graphite is 2:8-5:5. Within this range, hard carbon and graphite can cooperate and coordinate with each other, which is not only conducive to improving the transmission rate of lithium ions during charging, but also enables the negative electrode active material to have a higher first coulombic efficiency and stability, thereby further improving the discharge performance and cycle performance at low temperatures.
[0136] Illustratively, the mass ratio of hard carbon to graphite is 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 4.5:5.5 or 5:5.
[0137] Preferably, the particle size Dv50 of the hard carbon is 3 μm to 10 μm, and / or the specific surface area is 5 m 2 / g-10m 2 / g, and / or, the mass percentage of impurity elements in the hard carbon is not higher than 10ppm. Within this range, the hard carbon particles are relatively large and have a lower specific surface area, which is beneficial to reduce the film formation area of the SEI film on the hard carbon surface and improve the first coulomb efficiency and high temperature stability of the battery; at the same time, the impurity content of the hard carbon is low, which can ensure that the negative electrode active material has sufficient lithium storage space.
[0138] For example, the particle size Dv50 of the hard carbon is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm; the specific surface area is 5 m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g or 10m 2 / g.
[0139] The impurity elements in the hard carbon of the present invention include Fe, Co, Cu and Ni.
[0140] Preferably, the negative electrode active material layer comprises, by mass percentage: negative electrode active material
[0141] 90wt%-97wt%, binder 1wt%-3wt%, dispersant 1wt%-3wt%, conductive agent 1wt%-4wt%.
[0142] Hereinafter, a lithium ion battery including the positive electrode active material of the present invention will be described in detail through specific examples.
[0143] Example 1
[0144] 1) Preparation of positive electrode materials: Add raw materials ammonium metavanadate, ammonium dihydrogen phosphate and glucose into deionized water and stir evenly to obtain a slurry with a solid content of 38%. Then transfer the slurry to a sand mill for grinding to obtain a slurry with a particle size Dv50 of 268 nm.
[0145] The slurry prepared above was transferred to a pressure spray drying device, with an inlet air temperature of 190°C, an outlet air temperature of 90°C, and a compressed air pressure of 0.45 MPa to obtain a spherical precursor;
[0146] The spherical precursor prepared above was mixed evenly with lithium fluoride and placed in a roller kiln, first heated to 800°C at a heating rate of 3°C / min, kept at that temperature for 10 hours, and then cooled to room temperature at a rate of 3°C / min. The sintering atmosphere was nitrogen with a nitrogen purity of 99.99%. After sintering, the positive electrode active material of this embodiment was obtained;
[0147] Among them, the ICP test shows that the mass percentage of fluorine element is 15wt%, and the mass percentage of vanadium element is 25wt%; the SEM test shows that the average particle size of the secondary particles is 14.2μm, the major axis length a of the secondary particles is 14.3μm, the minor axis length b is 14.1μm, and the average particle size of the primary particles is 498nm; the carbon-sulfur analyzer test shows that the mass percentage of carbon material is 2wt%; the TEM test shows that the thickness of the coating layer is 20nm; the laser particle size test shows that the particle size Dv50 of the secondary particles is 13.5μm, and the particle size Dv90 is 35.8μm; the specific surface area of the secondary particles tested by the specific surface area tester is 19.2m 2 / g; at this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles is 28.5; measured by a micro compression tester, the mechanical strength of the secondary particles is 76MPa.
[0148] 2) Preparation of positive electrode sheet: a mixture of 91.5% positive electrode active material, 4% carbon black, 4% binder PVDF and 0.5% dispersant was uniformly dispersed in N-methylpyrrolidone (NMP), and stirred thoroughly to prepare positive electrode slurry; the positive electrode slurry was uniformly coated on the aluminum foil with a carbon coating layer on the surface using a coating machine, and the surface density of the coating layer was 9 mg / cm 2 After baking and rolling, the compacted density was 1.9 g / cm 3 The positive electrode;
[0149] 3) Preparation of negative electrode sheet: a mixture of 95% artificial graphite, 2% carbon black, 2% binder SBR, and 1% CMC was uniformly dispersed in deionized water to prepare negative electrode slurry; the negative electrode slurry was uniformly coated on the copper foil using a coating machine, and the surface density of the coating layer was 6 mg / cm 2After baking and rolling, the compacted density was 1.35 g / cm 3 The negative electrode;
[0150] 4) The electrolyte includes lithium hexafluorophosphate and an organic solvent, the organic solvent includes fluoroethylene carbonate and methyl trifluoroethyl carbonate, wherein the mass percentage of lithium hexafluorophosphate in the electrolyte is 9wt%, and the mass ratio of fluoroethylene carbonate to methyl trifluoroethyl carbonate is 6:4;
[0151] 5) Preparation of lithium-ion batteries: Repeat the stacking sequence of negative electrode sheet, separator, positive electrode sheet, and separator. The number of negative electrode layers is 21 and the number of positive electrode layers is 20. After stacking, use aluminum-plastic film to encapsulate and inject liquid. After aging, formation, and sorting steps, a lithium-ion battery with a battery capacity of 1.5Ah can be obtained.
[0152] Example 2
[0153] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the amount of lithium fluoride is adjusted so that the mass percentage of fluorine element in the prepared positive electrode active material is 10wt%.
[0154] Example 3
[0155] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the amount of lithium fluoride is adjusted so that the mass percentage of fluorine element in the prepared positive electrode active material is 20wt%.
[0156] Example 4
[0157] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the amount of ammonium metavanadate is adjusted so that the mass percentage of vanadium element in the prepared positive electrode active material is 20wt%.
[0158] Example 5
[0159] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the amount of ammonium metavanadate is adjusted so that the mass percentage of vanadium element in the prepared positive electrode active material is 30wt%.
[0160] Example 6
[0161] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Example 1, except that in step 1), the amount of glucose is adjusted so that the mass percentage of the carbon material in the prepared positive electrode active material is 1wt% and the thickness of the coating layer is 10nm.
[0162] Example 7
[0163] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the amount of glucose is adjusted so that the mass percentage of the carbon material in the prepared positive electrode active material is 3wt% and the thickness of the coating layer is 30nm.
[0164] Example 8
[0165] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Example 1, except that, in step 1), the slurry particle size Dv50, the air inlet temperature, air outlet temperature and compressed air pressure in the spray drying and the sintering conditions are adjusted so that in the prepared positive electrode active material, the average particle size of the secondary particles is 6.1 μm, the median particle size Dv50 is 5.2 μm, the particle size Dv90 is 32.4 μm, the average particle size of the primary particles is 204 nm, the major axis length of the secondary particles is 6.2 μm, the minor axis length is 6.0 μm, and the specific surface area of the secondary particles is 24.8 m 2 At this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles was 29.9.
[0166] Example 9
[0167] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the slurry particle size Dv50, the air inlet temperature, air outlet temperature and compressed air pressure in the spray drying and the sintering conditions are adjusted so that in the prepared positive electrode active material, the average particle size of the secondary particles is 13.8 μm, the median particle size Dv50 is 14.5 μm, the particle size Dv90 is 33.4 μm, the average particle size of the primary particles is 486 nm, the major axis length of the secondary particles is 13.8 μm, the minor axis length is 13.6 μm, and the specific surface area of the secondary particles is 12.7 m 2 At this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles was 28.4.
[0168] Example 10
[0169] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 1, except that, in step 1), the slurry particle size Dv50, the inlet air temperature, outlet air temperature and compressed air pressure in the spray drying and the sintering conditions are adjusted so that the median particle size Dv50 of the secondary particles in the positive electrode active material is 4.1 μm, and correspondingly, the average particle size of the secondary particles is 5.6 μm, the major axis length is 5.7 μm, the minor axis length is 5.6 μm, the particle size Dv90 is 28.4 μm, the average particle size of the primary particles is 256 nm, and the specific surface area is 26.8 m 2 At this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles was 21.9.
[0170] Embodiment 11
[0171] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 1, except that, in step 1), the slurry particle size Dv50, the inlet air temperature, outlet air temperature and compressed air pressure in the spray drying and the sintering conditions are adjusted so that the average particle size of the secondary particles in the positive electrode active material is 11.1 μm, the major axis length is 11.3 μm, the minor axis length is 11.1 μm, and the median particle size Dv50 is 10.8 μm. Correspondingly, the particle size Dv90 is 35.2 μm, the average particle size of the primary particles is 590 nm, and the specific surface area is 15.8 m 2 At this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles was 18.8.
[0172] Example 12
[0173] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the amount of ammonium metavanadate is adjusted so that the mass percentage of vanadium element in the prepared positive electrode active material is 32wt%.
[0174] Example 13
[0175] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 1, except that in step 1), the amount of glucose is adjusted so that the mass percentage of the carbon material in the prepared positive electrode active material is 4wt%, and accordingly, the thickness of the coating layer is 36nm.
[0176] Embodiment 14
[0177] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), vinylene carbonate (VC) is added to the electrolyte in an amount of 1% by mass, and the content of fluoroethylene carbonate in the electrolyte is correspondingly reduced.
[0178] Embodiment 15
[0179] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of vinylene carbonate (VC) in the electrolyte is adjusted to 0.5%, and the content of fluoroethylene carbonate in the electrolyte is increased accordingly.
[0180] Example 16
[0181] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of vinylene carbonate (VC) in the electrolyte is adjusted to 2%, and the content of fluoroethylene carbonate in the electrolyte is correspondingly reduced.
[0182] Embodiment 17
[0183] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of vinylene carbonate (VC) in the electrolyte is adjusted to 0.05%, and the content of fluoroethylene carbonate in the electrolyte is increased accordingly.
[0184] Embodiment 18
[0185] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of vinylene carbonate (VC) in the electrolyte is adjusted to 0.1%, and the content of fluoroethylene carbonate in the electrolyte is increased accordingly.
[0186] Embodiment 19
[0187] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of vinylene carbonate (VC) in the electrolyte is adjusted to 10%, and the content of fluoroethylene carbonate in the electrolyte is correspondingly reduced.
[0188] Embodiment 20
[0189] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 14, except that in step 4), the mass percentage of vinylene carbonate (VC) in the electrolyte is adjusted to 12%, and the content of fluoroethylene carbonate in the electrolyte is correspondingly reduced.
[0190] Embodiment 21
[0191] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 14, except that in step 3), the negative electrode active materials artificial graphite and carbon black are replaced by graphite and hard carbon (mass ratio is 3:7), the particle size Dv50 is 7.2 μm, and the specific surface area is 7.1 m 2 / g, the content of impurity elements is not higher than 10ppm, and the others remain unchanged.
[0192] Embodiment 22
[0193] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 21, except that in step 3), the mass ratio of graphite to hard carbon is 2:8, and the other parameters remain unchanged.
[0194] Embodiment 23
[0195] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 21, except that in step 3), the mass ratio of graphite to hard carbon is 5:5, and the other parameters remain unchanged.
[0196] Embodiment 24
[0197] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 21, except that in step 3), the particle size Dv50 of the hard carbon is adjusted to 3.4 μm and the specific surface area is 9.8 m 2 / g, and the rest remain unchanged.
[0198] Embodiment 25
[0199] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 21, except that in step 3), the particle size Dv50 of the hard carbon is adjusted to 9.6 μm and the specific surface area is 5.3 m 2 / g, and the rest remain unchanged.
[0200] Embodiment 26
[0201] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Example 21, except that in step 3), the mass ratio of graphite to hard carbon is adjusted to 1:9.
[0202] Embodiment 27
[0203] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 21, except that in step 3), the particle size Dv50 of the hard carbon is adjusted to 2.5 μm and the specific surface area is 11.7 m 2 / g.
[0204] Comparative Example 1
[0205] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that, in step 1), glucose is replaced by acetylene black, and the average particle size of the secondary particles in the prepared positive electrode active material is 23.1 μm, the major axis length is 23.5 μm, the minor axis length is 23.0 μm, and the average particle size of the primary particles is 650 nm. Correspondingly, the particle size Dv50 of the secondary particles is 21.5 μm, the particle size Dv90 is 42.1 μm, and the specific surface area is 36.2 m 2 At this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles was 35.5.
[0206] Comparative Example 2
[0207] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that in step 1), the amount of lithium fluoride is adjusted so that the mass percentage of fluorine element in the prepared positive electrode active material is 22wt%.
[0208] Comparative Example 3
[0209] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that in step 1), the amount of lithium fluoride is adjusted so that the mass percentage of fluorine element in the prepared positive electrode active material is 8wt%.
[0210] Comparative Example 4
[0211] The preparation method of the lithium-ion battery in this comparative example is basically the same as that in Example 1, except that, in step 1), the slurry particle size Dv50, the inlet air temperature, outlet air temperature and compressed air pressure in the spray drying and the sintering conditions are adjusted so that in the positive electrode active material, the average particle size of the secondary particles is 18.4 μm, the major axis length is 18.9 μm, the minor axis length is 18.3 μm, and the average particle size of the primary particles is 489 nm. Correspondingly, the particle size Dv50 of the secondary particles is 16.9 μm, the particle size Dv90 is 28.7 μm, and the specific surface area is 12.4 m 2 At this time, the ratio of the average particle size of the secondary particles to the average particle size of the primary particles was 37.6.
[0212] The basic parameters are shown in Tables 1 and 2.
[0213] Table 1
[0214]
[0215] Table 2
[0216]
[0217] Test example
[0218] 1. The lithium-ion battery in the above embodiment 1 is subjected to charge and discharge tests. The test results are shown in Figure 2 .
[0219] Figure 2 is the charge and discharge curve diagram of the lithium ion battery in Example 1, Figure 2 It can be seen that the lithium-ion battery in Example 1 has a relatively high platform voltage of 4.2 V, which is significantly higher than the platform voltage of a conventional lithium iron phosphate battery system (3.45 V). It can be seen that the positive electrode active material of the present invention can significantly increase the platform voltage of the battery and enable the battery to have a higher energy density.
[0220] 2. The low temperature discharge performance and cycle performance of the lithium ion batteries in the above embodiments and comparative examples were tested:
[0221] 1) Low temperature discharge performance
[0222] The battery prepared in the above embodiment and comparative example was charged and discharged for two cycles at 1C rate at room temperature 25°C, with a voltage range of 2.5-4.3V and a cut-off current of 0.05C. The discharge capacity of the second cycle was recorded as C0. Then it was charged to 4.3V at 1C rate, with a cut-off current of 0.05C, which was a fully charged state. After reaching the fully charged state, 20% of the electricity was discharged at 1C, that is, 80% SOC. The battery was left at -20°C for 4h. The discharge end voltage after 14.45C discharge for 0.3s, 9.25C discharge for 3s, and 6.2C discharge for 105s was tested in turn, with a sampling accuracy of 10ms; the cut-off voltage was 1V.
[0223] The test results are shown in Table 3 and Figure 3 .
[0224] Figure 3 is a bar graph of the cold start terminal voltage of the lithium ion battery in Example 1 and Comparative Example 1, Figure 3 It can be seen that at a low temperature of -20°C, the lithium-ion batteries in Example 1 and Comparative Example 1 were subjected to a cold start test (instantaneous high-rate discharge), and the voltages after discharge at 14.45C / 0.3s, 9.25C / 3s, and 6.2C / 105s were recorded respectively. The battery voltages in Example 1 were 3.30V, 3.03V, and 3.27V, respectively, while the battery voltages in Comparative Example 1 were 2.53V, 2.61V, and 2.39V, respectively, which were much lower than the low-temperature performance in Example 1.
[0225] 2) Normal temperature cycle performance
[0226] The lithium ion batteries in the above embodiments and comparative examples are charged and discharged for two cycles at a rate of 1C at room temperature of 25°C, with a voltage range of 2.5-4.3V and a cut-off current of 0.05C, and the discharge capacity at the second cycle is recorded as C0; the batteries are cycled for 500 cycles according to the above charge and discharge mechanism, and the discharge capacity after the cycle is recorded as C1, then the cycle capacity retention rate (%) = C1 / C0×100%.
[0227] The test results are shown in Table 3.
[0228] Table 3
[0229]
[0230] From Table 3, we can see that:
[0231] The lithium ion batteries in Examples 1 to 13 have higher discharge terminal voltage and room temperature cycle capacity retention rate than those in Comparative Examples 1 to 4, wherein the voltage after 14.45C / 0.3s discharge in Example 1 is 3.03V, the voltage after 9.25C / 3s discharge is 3.03V, the voltage after 6.2C / 105s discharge is 3.27V, and the capacity retention rate after 500 cycles is still 90.5%, which is significantly higher than the lithium ion batteries in Comparative Examples 1 to 4. It can be seen that the positive electrode active material in the present invention can effectively improve the low temperature discharge performance and cycle stability of the battery.
[0232] 3. The low-temperature discharge performance, cycle performance, and high-temperature storage performance of the lithium-ion batteries in Examples 1 and 14 to 20 were tested. The test methods for the low-temperature discharge performance and cycle performance were the same as those described above, and the test method for the high-temperature storage performance was as follows:
[0233] The lithium ion batteries in the above embodiments and comparative examples are charged and discharged for two cycles at a rate of 1C at room temperature of 25°C, with a voltage range of 2.5-4.3V and a cut-off current of 0.05C, and the discharge capacity of the second cycle is recorded as C0; then charged at a rate of 1C at room temperature to an upper limit voltage of 4.3V and a cut-off current of 0.05C, at which time the battery is fully charged; after storing the fully charged battery in a constant temperature box at 45°C for 60 days, it is discharged at a rate of 1C to 4.3V to obtain the residual capacity; then charged and discharged for two cycles at a rate of 1C, with a voltage range of 2.5-4.3V, and the discharge capacity of the second cycle is recorded as the recovery capacity, then the residual capacity retention rate is the ratio of the residual capacity to C0, and the recovery capacity retention rate is the ratio of the recovery capacity to C0.
[0234] The test results are shown in Table 4.
[0235] Table 4
[0236]
[0237] From Table 4, we can see that:
[0238] By adding vinylene carbonate to the electrolyte, it can be more compatible with the positive electrode active material and effectively improve the high-temperature storage performance of the battery. The high-temperature storage residual capacity retention rate of Example 14 can reach 86.1%, and the high-temperature storage recovery capacity rate can reach 88.4%. Moreover, the addition of vinylene carbonate does not have a negative impact on the low-temperature discharge performance and cycle stability of the battery, and its discharge terminal voltage and room temperature cycle capacity retention rate have hardly changed.
[0239] 4. The low-temperature discharge performance, cycle performance, high-temperature storage performance and first coulombic efficiency of the lithium-ion batteries in Examples 14 and 21 to 27 were tested, wherein the test methods for the low-temperature discharge performance, cycle performance and high-temperature storage performance were the same as those described above, and the test method for the first coulombic efficiency was as follows:
[0240] The first charge and discharge in the formation stage is taken as the first coulomb efficiency: the aged battery is charged to 4.3V at a constant current of 0.5C, and the charge capacity is recorded as C2; then it is discharged to 2.5V at 0.5C, and the discharge capacity is recorded as C3, then the first coulomb efficiency (%) = C3 / C2×100%. The test results are shown in Table 5.
[0241] Table 5
[0242]
[0243] From Table 5, we can see that:
[0244] The lithium-ion batteries in Examples 21 to 27 have higher high-temperature storage stability and first coulombic efficiency than those in Example 14, and the discharge terminal voltage and room temperature cycle capacity retention rate have not changed significantly, indicating that the use of graphite and hard carbon as negative electrode active materials can be more compatible with the positive electrode active materials, and can further improve the high temperature stability and first coulombic efficiency of the battery while ensuring a higher discharge terminal voltage and room temperature cycle performance.
[0245] 5. The positive electrode active material in the above embodiment 1 is subjected to scanning electron microscopy and energy spectrum analysis to obtain a SEM image and EDS energy spectrum of the positive electrode active material. The test results are as follows: Figure 4-Figure 12 shown.
[0246] Figure 4 is the SEM image of the positive electrode active material in Example 1 at 1.00K, Figure 5 is the SEM image of the positive electrode active material in Example 1 at 2.50k, Figure 6 is the SEM image of the positive electrode active material in Example 1 at 30.0K. Figure 4-Figure 6 It can be seen that the positive electrode active material is a spherical particle, and is formed by the aggregation of several primary particles.
[0247] Figure 7 is the EDS image of the V element of the positive electrode active material in Example 1, Figure 8 is the EDS diagram of the positive electrode active material P element in Example 1, Fig. 9 is the EDS image of the O element of the positive electrode active material in Example 1, Fig.10 is the EDS image of the C element of the positive electrode active material in Example 1, Fig.11 is the EDS image of the positive electrode active material F element in Example 1, Figure 7-Figure 11 It can be seen that the distribution uniformity of each element in the positive electrode active material in Example 1 is relatively high, especially the distribution of the C element therein is relatively uniform, without obvious regional differences. Combined with the data in Table 3 above, it can be seen that the carbon coating effect of the positive electrode active material in the present invention is good, which can effectively improve the electronic conductivity of the positive electrode active material and reduce the charge transfer impedance (Rct), thereby significantly reducing polarization, which is helpful to improve the low-temperature discharge performance of the battery.
[0248] Fig.12 This is a TEM image of the primary particles in the positive electrode active material in Example 6. As can be seen from Figure 6, there is a coating layer on the surface of the primary particles, that is, a carbon coating layer with a thickness of about 10 nm.
[0249] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes primary particles and secondary particles formed by agglomeration of the primary particles; the primary particles include a matrix material and a coating layer, the matrix material includes LiVPO4F, and the coating layer includes a carbon material; The mass percentage of fluorine element in the positive electrode active material is 10wt%-20wt%; The ratio of the average particle size of the secondary particles to the average particle size of the primary particles is 15-30.
2. The positive electrode active material according to claim 1, characterized in that The average particle size of the secondary particles is 1 μm-40 μm, and / or the average particle size of the primary particles is 200 nm-500 nm.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The mass percentage of vanadium element in the positive electrode active material is 20wt%-30wt%; And / or, the mass percentage of the carbon material in the positive electrode active material is 1wt%-3wt%; and / or, the carbon material comprises at least one of soft carbon, graphite, hard carbon, graphene, and carbon nanotubes; Preferably, the carbon material comprises soft carbon.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The positive electrode active material satisfies Formula 1, 1≤a / b≤1.2 Formula 1 In Formula 1, a is the length of the major axis of the secondary particle, in μm; b is the length of the minor axis of the secondary particle, in μm; Preferably, the length a of the major axis of the secondary particles is 0.5 μm to 50 μm, and / or the length b of the minor axis of the secondary particles is 0.5 μm to 50 μm.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The coating layer has a thickness of 1nm-30nm.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The particle size Dv50 of the secondary particles is 5 μm-20 μm, and the particle size Dv90 is 30 μm-40 μm; And / or, the specific surface area of the secondary particles is 12m 2 / g-25m 2 / g; And / or, the mechanical strength of the secondary particles is 30 MPa-80 MPa.
7. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 6; Preferably, the moisture content of the positive electrode sheet is less than 1000 ppm.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode active material according to any one of claims 1 to 6, or the positive electrode sheet according to claim 7.
9. The lithium-ion battery according to claim 8, characterized in that: The lithium-ion battery also includes an electrolyte; the electrolyte includes vinylene carbonate; Preferably, the mass percentage of the vinylene carbonate in the electrolyte is 0.1wt%-10wt%; More preferably, the mass percentage of the vinylene carbonate in the electrolyte is 0.1wt%-2wt%.
10. The lithium ion battery according to claim 8 or 9, characterized in that: The lithium-ion battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; The negative electrode active material in the negative electrode active material layer includes graphite and hard carbon; Preferably, the mass ratio of graphite to hard carbon is 2:8-5:5; Preferably, the particle size Dv50 of the hard carbon is 3 μm-10 μm, and / or the specific surface area is 5 m 2 / g-10m 2 / g.
Citation Information
Cited By
Lithium secondary battery, positive electrode active material and preparation method therefor, and electric device
WO2026174991A1